2019
DOI: 10.3389/fpsyg.2019.02780
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Mechanism of the Practice Effect of Time-Based Prospective Memory: The Role of Time Estimation

Abstract: Remembering to perform delayed intentions at a specific time point or period is referred to as time-based prospective memory (TBPM). The practice effect of TBPM is the phenomenon that TBPM performance improves via repeated PM training. In the present study, our main purpose was to explore the cognitive mechanism of the practice effect of TBPM, specifically the role of time estimation in the practice effect. We adopted a simple retrospective component of TBPM (pressing 1 key) in the present study, facilitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The accuracy of time estimation is easily affected by cognitive load, and people's ability to estimate time is lower in high-load conditions (Taatgen et al, 2007). Gan and Guo (2019) believed that people's time monitoring is closely related to their ability to estimate time. When performing TBPM tasks, people always make conservative time estimations first and then check the time for feedback.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of time estimation is easily affected by cognitive load, and people's ability to estimate time is lower in high-load conditions (Taatgen et al, 2007). Gan and Guo (2019) believed that people's time monitoring is closely related to their ability to estimate time. When performing TBPM tasks, people always make conservative time estimations first and then check the time for feedback.…”
Section: Discussionmentioning
confidence: 99%
“…At a more specific level, our framework also offers a more comprehensive and process‐oriented account of external time monitoring in the final stage of PM task, as compared to previous work that probed what happens near to the PM deadline using simpler indices (Gan & Guo, 2019; Guo & Huang, 2019; Jäger & Kliegel, 2008; Kliegel et al., 2005; Mioni & Stablum, 2014). Our results provided empirical corroboration to the seminal work of Atkin and Cohen (1996) about interval reduction, especially in the time interval closely preceding the PM deadline, thus highlighting participants’ rationality in external time monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…However, in their third study, a U-shaped rehearsal pattern was observed. Gan and Guo (2019) and Guo and Huang (2019) used an index of the overall proximity of clock checking to the temporal deadline, finding that participants checked the clock closer to the deadlines more often after a certain amount of practice in the TB PM task. Harris and Wilkins (1982) also observed an increase in the frequency of clock checking close to the deadline that was associated with response accuracy in a TB PM task (holding up response sheets at specific times while watching a movie).…”
Section: External Time Monitoring In Tb Pmmentioning
confidence: 99%
“…After that, a new TBPM task would restart at this time, and the procedure timing would start from 0:00. The procedure included four TBPM tasks, with a total of more than 120 trials of ongoing tasks lasting more than 5 min (Gan & Guo, 2019).…”
Section: Methodsmentioning
confidence: 99%